PERBEDAAN EFEKTIFITAS ANTIBAKTERI ANTARA EKSTRAK DAUN SIRIH MERAH (Piper crocatum) DAN EKSTRAK DAUN SIRIH HIJAU (Piper betle L.) TERHADAP Porphyromonas gingivalis - Dwianggraini W, Riezki; Pujiastuti, Peni; Ermawati, Tantin (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2013)
Almost people in the world got periodontal disease. It is about 50 % of adult population. Porphyromonas gingivalis (P. gingivalis) is anaerobic negative gram bacteria and played role in periodontitis, especially chronic periodontitis. Periodontal disease can be prevented by decreasing of plaque accumulation with oral rinse. Oral rinse can use traditional herbal, such as green and red betel leaf. Aim of this study was to know difference of antibacterial effectivity of green (piper betle l) and red (piper crocatum) betel leaf extract toward P. gingivalis. This research used well diffusion methods. There used 24 samples and divided 3 groups. First group used red betel leaf extract, second group used green betel leaf extract and third group used sterile aquadest. The samples were incubated for 24 hours in room temperature 37Â°C. Then, they were measured by inhibition zone by calipers. The result showed diameters of inhibition zone of green betel leaf was larger than red betel leaf and sterile aquadest. One way Anova test showed there was significant difference between the groups. The conclusion showed green betel leaf extract had antibacterial activity more than red betel leaf extract toward P. gingivalis.